2012
DOI: 10.1038/aja.2012.102
|View full text |Cite
|
Sign up to set email alerts
|

Silodosin is effective for treatment of LUTS in men with BPH: a systematic review

Abstract: The aim of this study was to systematically review the evidence on the efficacy and safety of silodosin treatments on lower urinary tract symptoms (LUTS) in men with benign prostatic hyperplasia (BPH) from randomized controlled trials. We searched PubMed (1966-December 2011), Embase (1974-December 2011 and the Cochrane Library Database (2011, Issue 12). The assessed outcome measures were the change from baseline for the International Prostate Symptom Score (IPSS), quality of life (QoL) score, peak urine maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…23 The previous meta-analysis showed that Silodosin is an effective therapy for lower urinary tract symptoms in men with BPH and is not inferior to 0.2 mg tamsulosin. 24 It is reported that ureteral contraction was regulated mainly by alpha-1A adrenoceptors in the hamster ureter. 25 Furthermore, Silodosin was demonstrated to have a higher selectivity for the alpha1A-AR subtype than tamsulosin hydrochloride, naftopidil, or prazosin hydrochloride, and the alpha1A-to-alpha1D binding ratio of Silodosin is 56:1.…”
Section: Discussionmentioning
confidence: 99%
“…23 The previous meta-analysis showed that Silodosin is an effective therapy for lower urinary tract symptoms in men with BPH and is not inferior to 0.2 mg tamsulosin. 24 It is reported that ureteral contraction was regulated mainly by alpha-1A adrenoceptors in the hamster ureter. 25 Furthermore, Silodosin was demonstrated to have a higher selectivity for the alpha1A-AR subtype than tamsulosin hydrochloride, naftopidil, or prazosin hydrochloride, and the alpha1A-to-alpha1D binding ratio of Silodosin is 56:1.…”
Section: Discussionmentioning
confidence: 99%
“…Ding et al 16 in a recent systematic review have also suggested that silodosin is effective therapy for LUTS in men with BPH and is not inferior to 0.2 mg tamsulosin.…”
Section: Discussionmentioning
confidence: 99%
“…In a metaanalysis, Ding et al reported consistently higher rates of ejaculatory dysfunction with silodosin compared with tamsulosin [63]. In a metaanalysis, Ding et al reported consistently higher rates of ejaculatory dysfunction with silodosin compared with tamsulosin [63].…”
Section: α-Adrenergic Antagonists and Sexual Dysfunctionmentioning
confidence: 99%